2022
DOI: 10.1021/acsami.2c08677
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Metal–Organic Framework-Based Cellular Scaffolds with High Protein Adsorption, Retention, and Replenishment Capabilities

Abstract: Metal–organic frameworks (MOFs) are porous materials with adsorption, storage, and separation capabilities due to their high specific surface areas and large pore volumes. MOFs are thus used in biomedical applications, and MOF nanoparticles have been widely studied as nanocarriers for drug delivery systems. Several research groups recently reported that specific MOF nanoparticles can adsorb and retain proteins, suggesting to us that MOF nanoparticles may have advantages as novel cell culture scaffolds. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 44 publications
1
7
0
Order By: Relevance
“…The dominant reason for the high protein retention may be π-π stacking and hydrophobic interactions of TA with hydrophobic amino acid residues of proteins [ 43 , 44 ]. The retention rate of protein on PNIPAAm-APTES coatings (sample V–VIII) decreased monotonously with time during the entire protein retention period, which was consistent with the report by Nagahama [ 45 ]. The protein retention rates of PNIPAAm 2000 -APTES-TA and PNIPAAm 1300 -APTES-TA in the first 12 h were 37.5% and 38.9%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The dominant reason for the high protein retention may be π-π stacking and hydrophobic interactions of TA with hydrophobic amino acid residues of proteins [ 43 , 44 ]. The retention rate of protein on PNIPAAm-APTES coatings (sample V–VIII) decreased monotonously with time during the entire protein retention period, which was consistent with the report by Nagahama [ 45 ]. The protein retention rates of PNIPAAm 2000 -APTES-TA and PNIPAAm 1300 -APTES-TA in the first 12 h were 37.5% and 38.9%, respectively.…”
Section: Resultssupporting
confidence: 91%
“…The adsorption of proteins is influenced by various surface physicochemical properties, including surface wettability, roughness, topography, charge, and chemistry [ 55 ]. While a hydrophobic surface promotes protein absorption, it may also cause denaturation of the absorbed proteins [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the mesopore created by AHT effectively improved protein absorption. Additionally, recent research has demonstrated that certain types of MOFs, such as UiO-66, possess remarkable protein adsorption and retention properties due to their large specific surface areas and pore volumes [ 55 , 56 ]. This is significant as protein adsorption serves as the primary stage in the implantation of scaffolds within living organisms and is crucial for subsequent biological processes [ 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations